Analisis Pendidikan Inklusi sebagai Tempat Pembelajaran terhadap Anak Penyandang Autisme SD Negeri Pegadungan 11 Pagi - Nurfadhillah, Septy; Khoerulnisa, Amelia; Riski, Muhammad; Zahra, Rahmiy Safira Az; Syahida, Salwa; Ariyani, Silva; Cahyani, Widya; Riflia, Wita (ALSYS, 2022)
The study aims to determine the role of inclusive school as places of learning for children with autism. The research used interviews and observations at Pegadungan 11 Pagi Elementary school. From the data that has been collected, the next step is to analyze it so that conclusions can be easily drawn. The result show that autism is adevelopmental disorder in children who are unable to communicate and express their feelings and desire. Usually this disorder is seen before the age of 3years. People with autism really need educational services that can accommodate, complate, yhe facilities and infrastructure they need, such as in inclisive schools. In inclusive schools, children with autism can learn independently and develop their abillity to communicate and develop social interaction skills, namelycommunicate well with their peers. So that incluive education is very necessary for children with autism in child development.